Airway Pressure and Transpulmonary Pressure During High-Frequency Oscillation for Acute Respiratory Distress Syndrome. Issue 2 (2014) - Henderson, William R; Dominelli, Paolo B; Griesdale, Donald EG; Talmor, Daniel; Sheel, A William
Abstract : BACKGROUND: High-frequency oscillation (HFO) is used for the treatment of refractory hypoxic respiratory failure. OBJECTIVE: To demonstrate that the mean transpulmonary pressure (PL ) cannot be inferred from mean airway pressure (mPaw). METHODS: In seven patients already undergoing HFO for refractory acute respiratory distress syndrome, esophageal pressure (Pes) was measured using an esophageal balloon catheter. Pleural pressure (Ppl) and PL were calculated from Pes. MAIN RESULTS: In the seven patients (mean [± SD] age 59±9 years) treated with HFO at 5±1 Hz and amplitude 75±10 cmH2 O, the mPaw was 27±6 cmH2 O, Ppl was 9±6 cmH2 O and PL was 18±11 cmH2 O. Successful catheter placement and measurement of Pes occurred in 100% of subjects. There was no correlation between PL and mPaw. The majority of subjects required hemodynamic support during the use of HFO; the frequency and degree of support during the study period was no different than that before the study. CONCLUSION: The present report is the first to describe measuring Pes and calculating Ppl during HFO for acute respiratory distress syndrome. While both current guidelines and recent trials have titrated treatment based on mPaw and oxygenation, there is wide variability in PL during HFO and PL cannot be predicted from mPaw.